(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Most educational models that prescribe teaching and training methods to groom school children into innovators fail to take a deeper view of engineering design methodology. Yet others tend to ignore the importance of human values which must be an integral part of any innovative design process. In this paper, We would first disaggregate design capabilities into its constituent capabilities, namely, exploring, creating and converging capabilities, which we need to master to produce better products and services, and then show how the cognitive and affective skills proposed by Benjamin Bloom, and Anderson and Krathwohl in their educational models can directly and significantly contribute to these constituent capabilities. With an improved understanding of the eco-system needed for better design solutions, we suggest that the present education systems, especially in developing countries, be critically reviewed and reoriented from the perspective of producing quality innovative designers, regardless of the problem area.